Respostas

2013-10-17T17:02:47-03:00
Escreva cada expressão da forma mais simples:
a) 5b²-12b²-11b²-(4b²+7b²)+b² =
    (5 -12 -11)b² - (4 + 7 + 1) b²   + b²  =     -18 b²  - 12 b²  + b²  = -29 b²   
b) (xz+yz-xy)-(2xy+2xz-12yz)+(6xy-14xz)
    xz + yz – xy  - 2xy – 2xz +2yz  +  6xy – 14xz = (1-2-14)xz + ( 1 + 2)  yz    +  ( -1 -2  + 6  ) xy  = -15xz -3yz + 3xy  
c) (x²-x-1)-(-x²+x+1)
x²- x – 1 + x²- x – 1 = (1 + 1) x² + ( -1-1)x -1-1 =            2x²  - 2x   - 2
1 5 1
Me ajudou bastante muito obrigada!!!